Exploring the utility of GPR to document the explosive history of old (> 100 ka) scoria cones - Leah Courtland; Vanessa Bump (Journal of Applied Volcanology)
Abstract Scoria cones are the most common volcanic landform on Earth. While eruptive styles range from effusive to explosive, the low-energy spectrum of activity is best documented. Hazards from these styles of eruption, including effusive and Strombolian styles as well as fountaining, are typically restricted to a relatively small area about the cone. However, it is the more explosive, violent Strombolian to sub-Plinian styles of eruption that result in sustained ash columns capable of disrupting aviation and distributing ash on the ground over larger regions. To increase our understanding of these higher-explosivity events, we must come to a better understanding of how commonly they occur, both temporally and geographically. Given that the scoria cone edifice itself is the longest-lasting remnant of any scoria cone eruption, it is important to use existing technologies to examine cone formation processes for evidence of sustained ash columns (indicative of regional hazards) within the geologic record. To this end, ground penetrating radar (GPR) techniques were employed at Crater Flat volcanic field, NV. While radar has previously been shown to be a valuable tool on fresh ( < 150 year old) scoria deposits, this work uses the technique on older ( > 100 ka) cones. Results indicate complex eruptive and erosive histories, and clearly indicate the utility of the GPR method in elucidating the stories of older cones and contributing to the growing body of knowledge concerned with high energy scoria cone volcanism.